Direct synthesis of N-methylurethanes from primary amines with dimethyl carbonate - Tundo, Pietro (2005)
The mechanism of the reaction between amines with dimethyl carbonate (DMC) has been investigated. Whereas in the absence of bases, they give methylation and carboxymethylation reactions without selectivity (BAl2 and B Ac2 mechanisms, respectively), in the presence of bases, the B Ac2 mechanism prevails. The carbamate already formed reacts further with DMC via the BAl2 mechanism to give the corresponding N-methyl derivative. Such pronounced double selectivity has been explained in terms of Pearson's Hard-Soft Acid-Base (HSAB) theory. Accordingly, N-methylcarbamates have been prepared from primary aliphatic and aromatic amines, either at reflux temperature of DMC (90 °C) or at 230 °C in autoclave. The reaction can be carried out in one step or through the isolation of the carbamate and the subsequent methylation reaction with DMC. This method is the direct synthesis, in high yield and selectivity, of secondary N-methylamines from the corresponding primary amines.